Cardiovascular risk factors are associated with increased lesion burden and brain atrophy in multiple sclerosis. Issue 2 (26th February 2015) - Kappus, Natalie; Weinstock-Guttman, Bianca; Hagemeier, Jesper; Kennedy, Cheryl; Melia, Rebecca; Carl, Ellen; Ramasamy, Deepa P; Cherneva, Mariya; Durfee, Jacqueline; Bergsland, Niels; Dwyer, Michael G; Kolb, Channa; et al.
Abstract : Background: Cardiovascular (CV) risk factors have been associated with changes in clinical outcomes in patients with multiple sclerosis (MS). Objectives: To investigate the frequency of CV risks in patients with MS and their association with MRI outcomes. Methods: In a prospective study, 326 patients with relapsing–remitting MS and 163 patients with progressive MS, 61 patients with clinically isolated syndrome (CIS) and 175 healthy controls (HCs) were screened for CV risks and scanned on a 3T MRI scanner. Examined CV risks included hypertension, heart disease, smoking, overweight/obesity and type 1 diabetes. MRI measures assessed lesion volumes (LVs) and brain atrophy. Association between individual or multiple CV risks and MRI outcomes was examined adjusting for age, sex, race, disease duration and treatment status. Results: Patients with MS showed increased frequency of smoking (51.7% vs 36.5%, p=0.001) and hypertension (33.9% vs 24.7%, p=0.035) compared with HCs. In total, 49.9% of patients with MS and 36% of HCs showed ≥2 CV risks (p=0.003), while the frequency of ≥3 CV risks was 18.8% in the MS group and 8.6% in the HCs group (p=0.002). In patients with MS, hypertension and heart disease were associated with decreased grey matter (GM) and cortical volumes (p<0.05), while overweight/obesity was associated with increased T1-LV (p<0.39) and smoking with decreased whole brain volume (p=0.049). Increased lateral ventricle volume was associated with heart disease (p=0.029) in CIS. Conclusions: Patients with MS with one or more CV risks showed increased lesion burden and more advanced brain atrophy.